PENGARUH KARAKTERISTIK PETERNAK TERHADAP ADOPSI TEKNOLOGI PEMELIHARAAN PADA PETERNAK KAMBING PERANAKAN ETTAWA DI DESA HARGOTIRTO KABUPATEN KULON PROGO - NURULIA HIDAYAH; CLARA AJENG ARTDITA; FAJAR BUDI LESTARI (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2019)
Livestock in Indonesia are mostly smallholder farms which have the following characteristics, including small scale businesses and using simple technology. One effort to overcome these problems is to carry out technological transformation. The introduction of technology for the maintenance of Peranakan Ettawa (PE) goats has been given to farmers, but not many of these technologies have been adopted by farmers who have certain characteristics. This study aims to analyze the characteristics of farmers who influence the technology adoption rates of Ettawa Peranakan goat breeding. The materials used were Peranakan Ettawa breeders who were members of the Mantep Makaryo, Subur and Tirto livestock groups in the village of Hargotirto, Kokap District, Kulon Progo Regency. The method used in this study is the survey method. The study was conducted from April to October 2018. The analysis used in this study is multiple linear regression analysis, namely the analysis used to determine the factors that influence the rate of technology adoption. The total respondents used in this study were 74 breeders. The results of the analysis showed that at the same time the characteristics of breeders, age, education level, number of family dependents, experience of breeding, number of lactation PE goats, and scale of ownership of PE goats had an influence on 67.20% goat maintenance technology adoption. Partially showing a significant effect (P <0.01) is the experience of farming, education level (P <0.05) while the number of dependents shows the effect on technology adoption (P <0.1). Keywords: Adoption, Characteristics of breeders, PE Goats